2019
DOI: 10.1002/jper.19-0034
|View full text |Cite
|
Sign up to set email alerts
|

The association between stage‐grade of periodontitis and sleep quality and oral health‒related quality of life

Abstract: Background Inadequate sleep increases inflammatory and proinflammatory markers among many other influences. Due to its potential to influence inflammation and oxidative stress, which are the main pathogenetic mechanisms actually recognized in the periodontal damage, poor sleep quality could be a factor for periodontitis and quality of life (QoL). In this context, the aim of this study is to investigate the association of stage‐grade of periodontitis with sleep quality. and the effect of periodontitis on QoL. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 41 publications
10
39
4
3
Order By: Relevance
“…prevalence of periodontitis. These results are consistent with recent findings in a Turkish population in which sleep duration was found to be associated with the stage and grade of periodontitis [22]. It also supports the findings of a study that used the Taiwan National Health Insurance database and found a 36% increase in the probability of developing periodontitis among the study sample [25].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…prevalence of periodontitis. These results are consistent with recent findings in a Turkish population in which sleep duration was found to be associated with the stage and grade of periodontitis [22]. It also supports the findings of a study that used the Taiwan National Health Insurance database and found a 36% increase in the probability of developing periodontitis among the study sample [25].…”
Section: Plos Onesupporting
confidence: 92%
“…A few recent studies had investigated the association between sleep duration and periodontitis with conflicting results, reporting negative, positive and no associations between sleep duration and periodontitis [21][22][23][24][25]. These studies had major shortcomings in the classification of the exposure and/or the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This study found no association between sleep behaviors and periodontal disease, consistent with a previously conducted study by Wiener et al, 23 although other studies did observe an association between these two risk factors for chronic disease. 24,26,45,46 A recently conducted clinical study correlated periodontitis with obstructive sleep apnea (OSA), a sleep disorder linked to cardiovascular disease through chronic intermittent hypoxia associated with sympathetic activation, oxidative stress, systemic inflammation, hypercoagulability, endothelial dysfunction, and metabolic dysregulation. 24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Poor and inadequate sleep is a risk factor that negatively impacts health outcomes and contributes to the development of inflammatory conditions such as obesity, diabetes, gingival inflammation and periodontal disease …”
Section: Introductionmentioning
confidence: 99%